Anticoccidial effects of a novel triazine nitromezuril in broiler chickens - Fei, Chenzhong; Fan, Chao; Zhao, Qiping; Lin, Yang; Wang, Xiaoyang; Zheng, Wenli; Wang, Mi; Zhang, Keyu; Zhang, Lifang; Li, Tao; Xue, Feiqun (Veterinary parasitology, 2013)
The anticoccidial efficacy of 2-(3-methyl-4-(4-nitrophenoxy)phenyl)-1,2,4-triazine-3,5(2H,4H)-dione (nitromezuril, NZL), a novel triazine compound, was evaluated in three different studies under experimental conditions. The anticoccidial efficacy was chiefly evaluated using the anticoccidial index (ACI). The resistance level was determined by calculating ACI, percentage optimum anticoccidial activity (POAA), reduction in lesion scores (RLS) and relative oocyst production (ROP). In the dose determination study (study A), NZL was added to the diet at doses of 1, 2, 3, 4, 5 and 6mg/kg to test its efficacy against coccidiosis caused by Eimeria tenella. Groups treated with NZL 1mg/kg feed could observe the faecal dropping scores and caecal lesions. ACIs of NZL-treated groups reached 179–199. In the study on the anticoccidial efficacy of 3mg/kg NZL in the diet (study B), only a few faecal oocysts and slight lesions were observed. NZL significantly promoted weight gain (WG) and reduced lesion scores (LS) compared to controls receiving diclazuril (DZL) (P<0.05). ACIs of NZL-treated groups were 193, 192, 191 and 163 for E. tenella, Eimeria necatrix, Eimeria acervulina and Eimeria maxima, respectively, whereas those of DZL-treated groups were 185, 176, 176 and 148. In the cross-drug resistance study (study C), ACIs of NZL and toltrazuril (TZL)-treated groups ranged from 188 to 204, which were significantly higher than those of DZL-treated groups (P<0.05). NZL- and TZL-treated groups were sensitive to experimentally induced DZL-resistant E. tenella, whereas DZL-treated groups showed complete resistance. No cross-resistance was observed between DZL and NZL or TZL. Based on the abovementioned studies, it was concluded that diets containing 3mg/kg NZL had an excellent efficacy in preventing coccidiosis in broiler chickens. The activity of 3mg/kg NZL in the diet was equal or superior to that of 1mg/kg DZL. These results are of great significance for the future applications of NZL; however, its actual mechanism of action remains unknown. NZL is a potential novel anticoccidial agent suitable for further development.